(NfORTEPIANNYJ SONATY bETHOWENAs (NmONOGRAFIQs - (N`(B.(NkREMLEWs ((NmOSKWAs (NkOMPOZITORs, 1970)
(NkNIGE O FORTEPIANNYH SONATAH bETHOWENA MOGUT BYTX RAZNOGO HARAKTERA I PROFILQ(B.s
Keywords: (NMONOGRAFIQs